Take back our future : an eventful sociology of the Hong Kong Umbrella Movement - Lee, Ching Kwan; Sing, Ming, 1960- (Book collections on Project MUSE., 2019)
"This book explains the contexts, causes and consequences of the 2014 Hong Kong Umbrella Movement, a 79-day mass occupation protest in one of the world's most affluent financial centers"--